1986
DOI: 10.1042/bj2370931
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of N1-acetylspermidine in heart and spleen of isoprenaline-treated rats

Abstract: N1-Acetylspermidine is not detectable in rat heart, but its content greatly increases after a single injection of isoprenaline (10 mg/kg), reaching a concentration of about 10 nmol/g of tissue 4 h after the treatment. Part of the accumulated N1-acetylspermidine was split to putrescine. Isoprenaline also caused an increase of N1-acetylspermidine in the spleen, where its concentration increased 3.5-fold 6 h after the catecholamine. The accumulation of N1-acetylspermidine was dependent on the dose of isoprenaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The acetylated polyamine is then oxidized by a flavin-dependent enzyme, polyamine oxidase (PAO), with the formation of the parent polyamine (putrescine or spermidine) and the oxidation products H202 and acetamidopropanal (Pegg, 1986). N1-SAT is a short-lived protein that is rapidly induced by a wide variety of stresses and trophic agents (Matsui et al, 1981;Danzin et al, 1982;Della Ragione & Pegg, 1983;Persson & Pegg, 1984;Stefanelli et al, 1986;Erwin & Pegg, 1986;Halline et al, 1989). This burst of oxidative polyamine catabolism may be part of a general cellular response to stressors, although there may be species-specific differences in the regulation and expression of PAO (Hirvonen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The acetylated polyamine is then oxidized by a flavin-dependent enzyme, polyamine oxidase (PAO), with the formation of the parent polyamine (putrescine or spermidine) and the oxidation products H202 and acetamidopropanal (Pegg, 1986). N1-SAT is a short-lived protein that is rapidly induced by a wide variety of stresses and trophic agents (Matsui et al, 1981;Danzin et al, 1982;Della Ragione & Pegg, 1983;Persson & Pegg, 1984;Stefanelli et al, 1986;Erwin & Pegg, 1986;Halline et al, 1989). This burst of oxidative polyamine catabolism may be part of a general cellular response to stressors, although there may be species-specific differences in the regulation and expression of PAO (Hirvonen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that SAT activity is increased by a number of factors, including hepatotoxins, hormones, lectins, growth factors and heat shock (Matsui & Pegg, 1980;Matsui et al, 1981;Danzin et al, 1982;Della Ragione & Pegg, 1984;Shinki et al, 1985;Steffanelli et al, 1986;Ekstrom et al, 1989;Harari et al, 1989a,b;Matsui-Yuasa et al, 1989). One possible unifying factor which might mediate stimulation by these agents is an increase in the free intracellular polyamine concentration, owing to the overproduction of polyamines or the release of intracellular polyamines from some Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat accepts electrons from cellular electron transfer systems and donates them to oxygen, forming superoxide anion in many tissues (23). Isoprenaline produces superoxide anion directly (22), and it also elevates the N1-acetyl-SPD levels in rat heart and spleen (25). In contrast, CC14, CHC13 and CH2C12 are changed into chloromethyl-free radicals through dehalogenation by cytochrome P-450 enzyme, especially in the liver (10, 17).…”
Section: Discussionmentioning
confidence: 99%